2021
DOI: 10.1021/acsomega.1c02808
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Porphyrin Nanofibers on ZnO Nanoparticles for the Enhanced Photocatalytic Performance for Organic Dye Degradation

Abstract: Synthesizing novel photocatalysts that can effectively harvest photon energy over a wide range of the solar spectrum for practical applications is vital. Porphyrin-derived nanostructures with properties similar to those of chlorophyll have emerged as promising candidates to meet this requirement. In this study, tetrakis(4-carboxyphenyl) porphyrin (TCPP) nanofibers were formed on the surface of ZnO nanoparticles using a simple self-assembly approach. The obtained ZnO/TCPP nanofiber composites were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of calcination temperature on the crystallinity of the ZnO particles analyzed. As seen in Figure 1(b), as the calcination temperature was increased from 500 to 800 °C, the crystalline structure of the nanoparticles was improved in which more intense and narrower peaks were observed [37] . More importantly, as the calcination temperatures goes up from 500 to 800 °C, the average crystalline sizes of the ZnO nanoparticles were enhanced, where the average crystalline sizes of ZnO‐450, ZnO‐500, ZnO‐600, ZnO‐700 and ZnO‐800 were calculated as 27.5 nm, 29.15 nm, 30.8 nm, 32.3 nm, 35.7 nm and 36.3 nm, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…As seen in Figure 1(b), as the calcination temperature was increased from 500 to 800 °C, the crystalline structure of the nanoparticles was improved in which more intense and narrower peaks were observed. [37] More importantly, as the calcination temperatures goes up from 500 to 800 °C, the average crystalline sizes of the ZnO nanoparticles were enhanced, where the average crystalline sizes of ZnO-450, ZnO-500, ZnO-600, ZnO-700 and ZnO-800 were calculated as 27.5 nm, 29.15 nm, 30.8 nm, 32.3 nm, 35.7 nm and 36.3 nm, respectively. Since there was sufficient ChemistrySelect thermal energy, the increase in the size of crystalline caused a higher nucleation rate and growth of nanoparticles, which is in accordance with other studies in the literature.…”
Section: Characterization Of Zno Nanostructuresmentioning
confidence: 97%
“…When the density of the electron cloud increased, the shielding effect of the metal atom on the internal electrons also increased. Therefore, the binding energy of the inner shell of the electron was reduced ( 40 , 41 ). In Fig.…”
Section: Resultsmentioning
confidence: 99%